Building a proposed educational program based on meaningful learning in acquiring mathematical concepts for sixth graders (Journal of the College of Basic Education, 2022)
This research aims to identify a proposal based on learning with meaning in the acquisition of mathematical concepts for sixth-graders of elementary mathematics. To achieve the research goal, the researcher followed the descriptive approach procedures and adopted the open questionnaire as a tool for his research, he directed several questions to a number of arbitrators specialized in educational and psychological sciences And methods of teaching mathematics, and include question and suggestions for the purpose of identifying strategies and methods that are included in the meaning-based learning of mathematics for the sixth grade of elementary. Included (11) strategies that range from cognitive theory, and (4) appropriate strategies have been selected The meaning of learning, the researcher directed a questionnaire to find out the opinions of researchers and arbitrators to determine the suitability of behavioral goals for the subjects of mathematics for the sixth grade of primary school, knowing that the number of curriculum topics to be taught to students includes (10) different topics, then the researcher built a proposed program according to the strategies Selected by the arbitrators for the content of mathematics for the sixth grade of primary school, the researcher (square Kay) used a statistical method to find out the extent of agreement of expert opinions on the chosen behavioral goals and plans for teaching.Accordingly, the researcher recommends several recommendations, including:The program is in accordance with the strategies chosen by the arbitrators for the content of the subjects of mathematics for the sixth elementary grade, and the researcher used square Kay as a statistical means to find out the extent of experts agreement on the chosen behavioral goals and teaching plans. Accordingly, the researcher recommends the following:1 - Experimenting with the proposed curriculum for sixth grade primary school students to learn about its effectiveness in acquiring mathematical concepts.2- The necessity of re-authoring the school curricula in a way that is compatible with the meaningful learning theory.The researcher suggested proposals, including:Conducting an experimental study to identify the effect of meaningful learning theory on achievement and mathematical performance for sixth-grade primary students.Conducting a study to identify the effectiveness of an educational program based on meaningful learning to acquire mathematical concepts for sixth-grade primary students